Optimizing diabetic retinopathy therapy with precision medicine: Can we do that in Indonesia? - Putri, Nazwa Septiriana; Barliana, Melisa Intan (Public Health Risk Assesment Journal, 2025)
Background: Diabetes is one of the most common diseases in the world, including in Indonesia. High blood sugar levels in diabetics can cause various complications, one of which is diabetic retinopathy. The treatment used in diabetic retinopathy does not fully provide the desired therapeutic effect in all patients. Therefore, a study was conducted on the prescription drug approach to optimize diabetic retinopathy therapy. Methods: This narrative review was conducted by searching articles that discuss three main focuses, including (1) why precision medicine (PM) can be implemented in diabetic retinopathy (DR); (2) the application, benefits, and components of PM for DR; and (3) challenges in its implementation in Indonesia. The included articles are articles published in national and international journals between 2014 and 2025. Findings: This study reveals that diabetic retinopathy is a complication of diabetes whose development can be influenced by genetic and environmental factors of the patient. Precision medicine can be applied in determining the best therapy for diabetic retinopathy by analyzing the clinical condition history, molecular and biochemical biomarkers of patients using artificial intelligence or machine learning. Conclusion: optimization of diabetic retinopathy therapy can be done with a precision medicine approach by analyzing genetic factors and patient environmental factors. However, there are still some challenges in its application in Indonesia including health service disparities, regulatory issues, technology, costs, and human resources. To develop precision medicine in Indonesia, Indonesia should develop equitable distribution in health services, conduct policy and research more on DM and PM, and collaborate with other countries. This narrative review has several limitations: literature search was limited to 3 database sources, we did not assess the quality of the articles, and implementation steps and solutions for PM implementation in Indonesia are only discussed in general, not specifically for DR. Future research can be carried out by discussing in more depth the specific steps of PM implementation for DR. Novelty/Originality of this article: Although personalized medicine has been in the spotlight in the global. Novelty/Originality of this article: Although personalized medicine has been in the spotlight in the global medical world, its specific application in the treatment of diabetic retinopathy in a country with limited resources and diverse demographics such as Indonesia is still not widely explored. The originality lies in adapting precision medicine as a high-tech solution for diabetic retinopathy, which is one of the public health challenges.